Representasi Makna Gender dalam Iklan MS Glow x Keanu Analisis Semiotika Ferdinand de saussure - Indriyani Indriyani; Indriati Yulistiani; Juandanilsyah Juandanilsyah; Bayquni Bayquni (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the representation of gender meaning in the MS GLOW x Keanu AGL advertisement titled